An analysis of lexical categories in the Castle on the hill song lyric from Ed Sheeran - Dita Mawar Hadi; Exlesia Pestaria L Toruan (LADU: Journal of Languages and Education, 2021)
Background:  It’s very important to learn about morphology because morphology is the study of word and sub-discipline of linguistics that study word, structure and form which has components such as lexical categories. This process can reduce ambiguity during the process of correcting the words in sentences. Purpose: This study investigated the lexical categories in the song lyrics of Ed Sheeran’s album “Divide” entitle castle on the hills. Design and methods: This study used a qualitative method. Process of collecting data used to identify lyric that has lexical categories. The researcher used some of the lyrics of Ed Sheeran’s album as the data source. The technique of collecting data was content analysis. Results: The results of the research showed that cases of lexical categories. Based on the data analysis in the song lyrics of Ed Sheeran’s. There are 13 words noun, there are 5 words adjective, there are 7 words verb, there are 3 words adverb, and there are 4 words preposition